A Preservice Teacher's Experiences Teaching English Abroad: From ESL to EFL - M. Martha Lengeling; Melanie L. Schneider (Universidad Nacional de Colombia, 2023)
Although an international teaching practicum is assumed to broaden teacher candidates' cultural, linguistic, and pedagogical knowledge, the nature of this growth and its relation to teacher education practices have yet to be fully explored. Using a sociocultural perspective and drawing on the concepts of teacher socialization and a growth mindset, this qualitative case study investigates the experiences of a U.S. preservice teacher teaching English in a Mexican primary school. Analysis of teaching observations, the participant's reflections, and an interview revealed the teacher's growing sensitivity to the teaching context. She gradually recognized the differences between teaching English in the two countries, prompting a shift in pedagogy to one more compatible with teaching English as a foreign language. The importance of teaching context on teacher socialization is also examined.